A Case of Posterior Cortical Atrophy Presenting with Mood and Psychotic Symptoms - Tremearne Hotz; Manu Sharma; Bharat Narapareddy (Case Reports in Psychiatry)
Posterior cortical atrophy (PCA) is a rare neurodegenerative disorder characterized by predominant visual deficits due to its atrophy of the occipital lobes. Patients typically have preserved cognitive function during the early stages, making diagnosis more difficult when compared to other neurocognitive disorders. In this case, the patient presented predominantly with mood symptoms, delusions, and visual hallucinations. The disease course began 5 years ago with anxiety and insomnia. It developed into depressive symptoms including two suicide attempts (SAs), paranoia, and hallucinations. The diagnosis was eventually reached utilizing a thorough clinical exam, neuropsychological testing, MRI, positron emission tomography (PET), and dopamine transporter (DAT) scans. We conclude that mood or psychotic symptoms that emerge, escalate, or change dramatically at later ages merit further workup to evaluate for underlying neurodegenerative disorders.